Kompetensi SDM, Peran Industri 5.0, Literasi Digital Terhadap Kinerja Organisasi Dimediasi Motivasi Belajar Karyawan PT XYZ - Halimatusa’diah Halimatusa’diah; Dewi Puspaningtyas Faeni; Novita Wahyu Setyawati; Achmad Fauzi; Murti Wijayanti (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine HR competencies, the role of industry 5.0, and digital literacy on organizational performance through (mediated) learning motivation of PT XYZ employees. This research method is descriptive quantitative type by distributing questionnaires (Likert scale 1-5) to a sample size of 83 out of 500 respondents calculated using the Slovin formula and processed with SmartPLS 3.0 software. The results showed that the path coefficient and p-value of the HR Competency variable (0.191 and 0.002), the Role of Industry 5.0 (0.077 and 0.062), and Digital Literacy (0.150 and 0.025). This means that HR Competencies and Digital Literacy partially have a significant positive effect on the Organizational Performance of PT XYZ through (mediated) Employee Learning Motivation. While the Role of Industry 5.0 partially has no effect on the Organizational Performance of PT XYZ through (mediated) Employee Learning Motivation. Furthermore, the path coefficient and p-value of the Employee Learning Motivation variable are 0.410 and 0.002. This means that Employee Learning Motivation has a significant positive effect on the Organizational Performance of PT XYZ.